Systematic Literature Review: Pengaruh Virtual Leadership Terhadap Work Engagement Pada Karyawan dalam Setting Kerja Virtual - Zduroikhan, Taufiq (Flourishing Journal, 2025)
Technological developments have driven the increase in virtual work globally, but low employee work engagement is a major challenge due to suboptimal communication and virtual leadership. This study aims to analyze the effect of virtual leadership on employee work engagement in a virtual work setting through a systematic literature review approach. By utilizing two major databases, Google Scholar and Science Direct, this study identified 600 relevant scientific articles. After going through a rigorous screening process, including the elimination of duplicates and evaluation of titles and abstracts, 16 articles were selected for further analysis, and finally 4 main articles were synthesized. This study reveals that effective virtual leadership, characterized by intensive communication, mental support, training, and the use of ideal digital platforms, plays a significant role in increasing employee work engagement. However, challenges such as low employee work engagement due to suboptimal communication and the need for an adaptive leadership approach are still major obstacles. This study highlights the importance of developing a targeted virtual leadership strategy to strengthen work engagement in the digital era. AbstrakPerkembangan teknologi telah mendorong peningkatan pekerjaan virtual secara global, namun rendahnya work engagement karyawan menjadi tantangan utama akibat komunikasi dan kepemimpinan virtual yang tidak optimal. Penelitian ini bertujuan untuk menganalisis pengaruh virtual leadership terhadap work engagement karyawan dalam pengaturan kerja virtual melalui pendekatan sistematic literature review. Dengan memanfaatkan dua basis data utama, Google Scholar dan Science Direct, penelitian ini mengidentifikasi sebanyak 600 artikel ilmiah yang relevan. Setelah melalui proses penyaringan ketat, termasuk penghapusan duplikasi dan evaluasi judul serta abstrak, 16 artikel dipilih untuk dianalisis lebih lanjut, dan akhirnya 4 artikel utama disintesiskan. Penelitian ini mengungkap bahwa virtual leadership yang efektif, ditandai oleh komunikasi intensif, dukungan mental, pelatihan, dan penggunaan platform digital yang ideal, berperan signifikan dalam meningkatkan work engagement karyawan. Namun, tantangan seperti rendahnya keterikatan kerja karyawan akibat komunikasi yang kurang optimal serta kebutuhan akan pendekatan kepemimpinan yang adaptif masih menjadi kendala utama. Penelitian ini menyoroti pentingnya pengembangan strategi virtual leadership yang terarah untuk memperkuat keterlibatan kerja di era digital.